‘Picking up the pieces’: primary care practitioners’ experiences of cancer care reviews. A descriptive qualitative study - Dipesh P Gopal; Stephanie JC Taylor; Ping Guo; Nikolaos Efstathiou (BJGP Open)
Background: The number of people who are living with and beyond cancer is increasing in England. Primary care delivers cancer care via structured proactive conversations which are incentivised through the Quality and Outcomes Framework (QoF): ‘cancer care reviews’ (CCRs). Declining workforce numbers, increasing patient demand, CCR policy changes in 2020, and the onset of the coronavirus disease 2019 (COVID-19) pandemic motivate exploration of how staff deliver CCRs. Aim: To explore primary care staff’s experiences with CCRs, their view of CCRs, how they conduct CCRs, and their perception of the value of CCRs. Design & setting: Descriptive qualitative study in general practices in England. Method: Semi-structured online interviews with 15 primary care staff; data analysis using reflexive thematic analysis. Results: Four themes were identified: varied and evolving perception of cancer; the delivery and impact of CCRs; changes to CCR delivery during the COVID-19 pandemic; and ways to complement CCRs. Primary care staff felt that the way that cancer was perceived by patients, including those from ethnic minority backgrounds, impacted how CCRs were delivered. Cancer care involved acknowledging the challenge of a cancer diagnosis, helping decode jargon, and addressing unmet care needs. The pandemic resulted in remote CCR delivery for some practices. Staff suggested that community cancer teams could provide cancer care alongside existing services. Conclusion: Staff adopted the new 3- and 12-month format CCRs despite the COVID-19 pandemic. Clinical staff may benefit from better training on cancer as a long-term condition and how cancer is perceived by people from diverse ethnic backgrounds.